No Surrender : Skink #7 - Hiaasen, Carl (New York : Alfred A. Knopf, 2014)
With the help of an eccentric ex-governor, a teenaged boy searches for his missing cousin in the Florida wilds.
Keywords: Mystery and detective stories; Missing children -- Fiction; Wilderness areas -- Fiction; Florida -- Fiction